Towards Sustainable Urban Landscape Management: Floridians’ Perceptions of Residential Landscapes and Their Maintenance Requirements - Hayk Khachatryan; Alicia Rihn; Xumin Zhang; Michael Dukes (EDIS)
This 5-page fact sheet written by Hayk Khachatryan, Alicia Rihn, Xumin Zhang, and Michael Dukes and published by the UF/IFAS Food and Resource Economics Department is the first in a series from the Sustainable Residential Landscape Project, a study conducted in 2016 to address perceptions of landscapes in Florida, different factors that could influence the adoption of more sustainable landscape options, and ways to promote sustainable landscaping options. The Sustainable Residential Landscape Project was funded by the UF/IFAS Center for Landscape Conservation and Ecology (CLCE).